Taxonomic description of in situ bee pollen from the middle Eocene of Germany. Issue 1 (2nd January 2017) - Grímsson, FriĐgeir; Zetter, Reinhard; Labandeira, Conrad C.; Engel, Michael S.; Wappler, Torsten
Abstract: The middle Eocene Messel and Eckfeld localities are renowned for their excellently preserved faunas and diverse floras. Here we describe for the first time pollen from insect-pollinated plants found in situ on well-preserved ancient bees using light and scanning electron microscopy. There have been 140 pollen types reported from Messel and 162 pollen types from Eckfeld. Here we document 23 pollen types, six from Messel and 18 from Eckfeld (one is shared). The taxa reported here are all pollinated by insects and mostly not recovered in the previously studied dispersed fossil pollen records. Typically, a single or two pollen types are found on each fossil bee specimen, the maximum number of distinct pollen types on a single individual is five. Only five of the 23 pollen types obtained are angiosperms of unknown affinity, the remainder cover a broad taxonomic range of angiosperm trees and include members of several major clades: monocots (1 pollen type), fabids (7), malvids (4), asterids (5) and other core eudicots (1). Seven types each can be assigned to individual genera or infrafamilial clades. Since bees visit only flowers in the relative vicinity of their habitat, the recovered pollen provides a unique insight into the autochthonous palaeo-flora. The coexistence of taxa such as Decodon, Elaeocarpus, Mortoniodendron and other Tilioideae, Mastixoideae, Olax, Pouteria and Nyssa confirms current views that diverse, thermophilic forests thrived at the Messel and Eckfeld localities, probably under a warm subtropical, fully humid climate. Our study calls for increased attention to pollen found in situ on pollen-harvesting insects such as bees, which can provide new insights on insect-pollinated plants and complement even detailed palaeo-palynological knowledge obtained mostly from pollen of wind-pollinated plants in the dispersed pollen record of sediments. In the case of Elaeocarpus, Mortoniodendron, Olax and Pouteria the pollen collected by the middle Eocene bees represent the earliest unambiguous records of their respective genera.